REGIONAL ECOSYSTEM OF USED COOKING OIL (UCO) MANAGEMENT IN CENTRAL JAVA PROVINCE - Dewi, Dian Ayunita Nugraheni Nurmala; Iskandar, Deden Dinar (Universitas Tidar, 2023)
Indonesia is listed as the world's most used cooking oil (UCO) producing country. Biodiesel from UCO blends is claimed to have lower carbon emissions. A regional scale of sustainable UCO collection and processing ecosystem needs to be established to enhance the role of local authorities in the circular economy. Central Java has the potential for ecosystem planning for UCO management with a circular economy approach. Central Java Province has a total UCO potential of 36,217 kilo liters and can be used for biodiesel potential of 27,094 kilo liters per year. If it is assumed that the processing cost is IDR 9,000.00/liter. The biodiesel production cost for a year is IDR 243.86 trillion/year. Total revenue assumption of IDR 298.04 trillion/year (base price IDR 11,000.00/liter). The profit gain is IDR 54 trillion/year or IDR 4.5 billion/month. The B/C ratio of biodiesel processing is 0.22 and is considered profitable. This program is called Turn Oil On (TOOn). Keywords: Used cooking oil, Biodiesel, Circular economy, Central Java